Application of Hantzsch Reaction as a New Method for Spectrofluorimetric Determination of Some Cephalosporins - Mohamed A. El-Hamda, Ramadan Alia, Ahmed M. Haredyb, Hytham M. Ahmedc, Sayed M. Derayeab, Osama H. Abdelmageedb , d (Journal of Applied Pharmaceutical Science, 2017)
A selective spectrofluorimetric method was described for determination of some cephalosporins namely, cefadroxil, cefaclor, cefixime, cefpodxime, and cefepime. These drugs were utilized as a source of amine group to react with acetylacetone and formaldehyde reagents via a Hantzsch reaction. The fluorescence intensity of the reaction products were measured at an emission wavelength of482 nm after excitation at a wavelength of 415 nm. The linear calibration graphs were obtained in the concentration ranges of 1-100 µg/mL for either cefadroxil or cefaclor and 1-50 µg/mL for the other three drugs. The limits of detection and quantitation were in the concentration range of 0.31-0.82 and 0.72-2.5 µg/mL, respectively. The percent of relative standard deviation (at 50 µg/mL concentration level, n = 5) were in the range of 0.41-1.70% and 1.51-1.95% for intra-day and inter-day precision, respectively. The method was successfully applied for the assay of some dosage forms of the cited drugs and the results obtained were comparable with those obtained by a reported method.
Keywords: Spectrofluorimetric method, Cephalosporins, Acetylacetone, Formaldehyde, Hantzsch reaction, Dosage forms.